Investigation of Exercise Behavior Changes and Body Weight in The University students - Coşkun, Ali (Progress in Nutrition, 2022)
Aim: The aim of this research was to examine the stage of exercise behavior changes in students who were in different faculties. Methods:A total of 654 students from Çanakkale Onsekiz Mart University were included in this research. Stage of Exercise Behavior Change Questionnaire was used in the study. SPSS 20.0 package program was used for evaluation of scale data.  The data are given in frequency and percentage distribution. Results: The percentage of students at continued to exercise stage in Faculty of Agricalture is %13,50, Faculty of Communication  is 26,10%, Faculty of Education is 10,60%, Science Faculties is 13,90%, Faculty of Theology is 38,60, Faculty of Art is 16,30% and faculty of engineer is 16,50%.The percentage of students at precontemplation stage in Faculty of Agriculture is 11,50%, in Faculty of Communication is  16,30%, Faculty of Education is 16,50%, in Faculty of Science 13,90%, Faculty of Teology is 8,90%, Faculty of Arts  is 20,70%, faculty of engineer is 17,50%. There was a significant difference between the faculties in the maintenance stage (p0,05). As a result, the most students were in the Faculty of Theology at the maintenance stage. The units with the most students at the precontemplation stage were in the Faculty of Agriculture.